2000
DOI: 10.1121/1.428645
|View full text |Cite
|
Sign up to set email alerts
|

Use of higher order statistics in source signature estimation

Abstract: Higher order statistical blind deconvolution methods are implemented for use in removing multipath distortion from passively received underwater acoustic transient signals. Using single channel data and simulations, it is demonstrated that a fourth order method based on cumulant maximization can work well if the associated multipath Green's function is sufficiently "sparse." The iterative method is parameterized by filter length, and while there is a range of values at which the best solutions are obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The rotated component matrix can be used to enhance the result of PCA and discover the best pattern of loadings in a manner that is simpler to interpret (Reinard, 2006). A recommended approach which is known as the Varimax was used to improve the results by maximizing the loading of each variable on one of the extracted components whilst minimizing its loading on all the other components (Broadhead, Pflug and Field, 2000). Prior to analysing the data, it is important to check the reliability of measurement scale of the questionnaire and the appropriateness of factor analysis.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The rotated component matrix can be used to enhance the result of PCA and discover the best pattern of loadings in a manner that is simpler to interpret (Reinard, 2006). A recommended approach which is known as the Varimax was used to improve the results by maximizing the loading of each variable on one of the extracted components whilst minimizing its loading on all the other components (Broadhead, Pflug and Field, 2000). Prior to analysing the data, it is important to check the reliability of measurement scale of the questionnaire and the appropriateness of factor analysis.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…Other researchers have employed statistical techniques, like higher order statististics 5 and minimum entropy deconvolution ͑MED͒. 6 For the case of a shallow water channel with long observation distances ͑for which many modes are excited͒, one requires a large array of receivers for the channel Green's function to satisfy the requirements of these methods. In addition to work on channel deconvolution, Runkle et al 7 have demonstrated that classification accuracy may be greatly improved by fusing scattering data from multiple orientations around a target, via a hidden Markov model ͑HMM͒.…”
Section: Introductionmentioning
confidence: 99%
“…Wiggins' technique can be recast using non-Gaussianity as the statistical feature of the multipath function that is reduced (i.e., made more Gaussian) by the process of convolution. Maximization of the V-norm leads to an iterative technique that has been shown to be quite sensitive to noise [8].…”
Section: Vw-i>v I>7mentioning
confidence: 99%